Escherichia coli Spheroplast-Mediated Transfer of pBR322 Carrying the Cloned Ruminococcus albus Cellulase Gene into Anaerobic Mutant Strain FEM29 by Protoplast Fusion - Chen, Wei (1988)
Intergeneric protoplast fusion between Escherichia coli HB101 with pBR322 carrying the cloned o-(carboxymethyl)cellulase (CMCase) gene of Ruminococcus albus (Pro(-) Leu(-) Ap(r) Km(s)) and an anaerobic mutant strain, FEM29 (Trp(-) His(-) Ap(s) Km(r)), with dehydrodivanillin-degrading activity was performed in the presence of 40% polyvinyl alcohol 300 under aerobic and anaerobic conditions to transfer the cloned cellulase gene into the mutant. The mutant FEM29 had a unique property. When it was incubated in liquid medium with 1% glucose and sucrose, protoplasts could be produced autogenously and regenerated on the agar slant. E. coli spheroplasts formed from a plasmid-amplified overnight culture after 10 min of treatment with lysozyme (20 μg/ml) in a hypertonic solution (0.01 M Tris hydrochloride [pH 7.5], 0.4 M mannitol). Protoplast regeneration rates of FEM29 and HB101 were 30 and 83%, respectively, on the agar-yeast extract medium. Ap(r) Km(r) fusants were obtained at high frequency: 1.7 × 10(−2) anaerobically and 8.2 × 10(−3) aerobically. These fusants showed 23 to 57% of CMCase and dehydrodivanillin-degrading activities, respectively, as compared with parental strains. All the fusants isolated were gram-negative rods with main phenotypes such as urease and catalase activities as in HB101 and esterase and chymotrypsin activities as in FEM29. Southern hybridization experiments suggested that pBR322 with the cloned CMCase gene existed autonomously in the fusant cells. This is the first report describing transfer of pBR322 with a cloned cellulase gene into an anaerobic mutant by polyvinyl alcohol-mediated fusion with an E. coli spheroplast.